Determination of Harvesting Cycle of Gliricidia sepium for Bioenergy Using Growth Model - Diono, Dimas Wahyu; Rusolono, Teddy; Bahruni, Bahruni (Jurnal Ilmu Kehutanan, 2025)
The emission of CO2 is increasing due to the high population and standard of living, particularly from the energy sector. Renewable energy from forest resources, such as fuelwood, can contribute to these emissions' reduction. Therefore, this research aimed to generate a growth model to determine the harvesting cycle of Gliricidia sepium as a source of raw material for bioenergy. The model generation employed regression technique and used stand inventory data. The growth model for Gliricidia sepium was Y = 157.46e (-3.342/A), where age (A) was the independent variable. The optimum harvest occurred at 4 years with a biomass production potential of 68.28 tons/ha. This research provided valuable information for decision-making in managing the industrial forest plantation of Gliricidia sepium for bioenergy.